Phytophthora Identification and Sampling in Citrus Nurseries - Jamie D. Burrow; Diane B. Bright; Tim D. Riley; Evan G. Johnson; James H. Graham (EDIS)
Phytophthora species are important soilborne, fungus-like pathogens that attack the root systems, trunk, and fruit of citrus trees at any age. The front of this identification sheet includes images of healthy and infested roots and descriptions of leaf and root symptoms. The back lists sampling procedures: soil collection, soil testing, and diagnosing phytophthora. Written by Jamie D. Burrow, Diane B. Bright, Tim D. Riley, Evan G. Johnson, and James H. Graham, and published by the UF/IFAS Plant Pathology Department, July 2019. Update of original July 2015 publication. https://ufdc.ufl.edu/IR00008736/00001